RUMAH RAMAH BANJIR DI KAMPUNG PEJATEN TIMUR - Angie Abigail Setiawan (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Floods in Jakarta occur almost every year. Some areas even experienced floods which were quite severe and worrying, while the conditions for the evacuation were still not sufficient. Based on the data obtained, the largest flood point in Jakarta is in the South Jakarta area with 39 flood points and one of the areas experiencing the worst flooding in Jakarta is Kampung Pejaten Timur. East Pejaten Village has a low land contour. As a result, flooding in East Pejaten Village can reach 2-3 meters. Floods in Jakarta occurred because the principle of the city is still against the flood. Thus, the principle of a suitable building is a building that resists flooding and must be able to live with floods, because Jakarta floods are unavoidable. Several things need to be considered when designing buildings, including the residents' needs during the flood, the residents' activities during and during the flood, and the materials used in the project to support flood-resistant buildings. For this reason, the method used in designing is to adapt the activities of residents when it is flooded or not flooded into the building. To build a flood-friendly building, this project was designed as an amphibious building that can adapt to flooding by floating, and become a stilt house when it is not flooded. Thus, the residents who live in it no longer need to evacuate and their homes are also safe when floods come. Keywords:  Flood, Pejaten Timur, Residential AbstrakBanjir di Jakarta terjadi hampir setiap tahunnya. Beberapa daerah bahkan mengalami banjir yang cukup parah dan mengkhawatirkan, sedangkan kondisi pengungsian juga masih belum memadai. Berdasarkan data yang diperoleh, titik banjir terbanyak di Jakarta berada di daerah Jakarta Selatan dengan 39 titik banjir dan salah satu daerah yang mengalami banjir terparah di Jakarta adalah Kampung Pejaten Timur. Kampung Pejaten Timur memiliki kontur tanah yang rendah. Akibatnya, banjir di Kampung Pejaten Timur dapat mencapai 2-3 meter. Banjir di Jakarta ini terjadi karena prinsip kotanya yang masih melawan air. Maka, prinsip bangunan yang cocok adalah bangunan yang tidak melawan banjir dan harus mampu hidup berdampingan dengan banjir, karena banjir Jakarta tidak dapat dihindari. Ada beberapa hal yang perlu diperhatikan ketika mendesain bangunan, antara lain; kebutuhan warga ketika banjir, aktivitas warga setempat baik ketika banjir maupun tidak banjir, serta bahan dan material yang digunakan dalam proyek untuk memungkinkan bangunan tahan terhadap banjir. Untuk itu metode yang digunakan dalam mendesain adalah dengan mengadaptasikan aktivitas warga ketika banjir ataupun tidak banjir kedalam bangunan. Dalam upaya membangun bangunan ramah banjir, proyek ini dibuat sebagai bangunan amfibi yang mampu beradaptasi, dengan dapat mengapung ketika banjir dan menjadi rumah panggung ketika tidak banjir. Dengan demikian, warga yang tinggal didalamnya tidak perlu lagi mengungsi dan rumah mereka juga aman ketika banjir datang.